1295 Virtual Fracture Clinic: An Audit of Referral Quality and Service Effectiveness. (12th October 2021) - Beoku-Betts, C; Prodromidis, A; Nazar, A; Sharma, D; Barton, S
Abstract: Aim: Assessment of referral quality to the virtual fracture clinic (VFC) at the Liverpool University Hospital foundation trust compared to the standards set out by the Glasgow virtual fracture clinic pathway. As a secondary aim the effectiveness of the VFC in diverting patients not requiring further clinical management away from face-to-face specialist physical fracture clinics (PFC) was assessed. Method: Outcomes of 1st attendances were collected for standard PFC's before the implementation of the VFC at our centre. This data was comparatively analysed to the outcomes of 1st 'attendances' of VFCs post-service implementation. To assess VFC referral quality fracture type was recorded and compared to the standard set out by the Glasgow virtual fracture pathway which states that a selection of simple stable fractures should be discharged from ED directly with patient advice and telephone support. Results: We analysed 529 PFC first attendances and 402 VFC first attendances. We saw a variety of simples stable fractures (21%) in the VCF including: Distal radial, Fifth metatarsal, Minor radial head, Fifth metacarpal, Mallet finger, which could have been managed with direct ED discharge and telephone support. 19.4% of PFC attendance resulted in discharge without a change in management as compared to 22.1% of 1st attendances for the VFC. Conclusions: The VFC clinic has shown itself as an effective service in re-directing patients from face-to-face appointments, evidenced by the comparative rates of patient discharge on first attendance. This study has laid the foundation for improving referral quality to the VFC. Collaborative efforts between Orthopaedics and ED could improve VFC clinic efficiency further.